Tantangan dan Peluang Dakwah Masa Pandemi di Gampong Lampuja - Auliana Putri, Safna; Fakhruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The existence of da'wah is very important in human life, especially during a pandemic like this. Da'wah from time to time experiences dynamics along with human development. Da'wah emphasizes the task and process of how to convey Islamic teachings with full sincerity through various means and media. The presence of information technology is also the top platform for media in preaching. Da'i is the main factor in receiving maximal da'wah messages by mad'u, this is also a challenge and opportunity in preaching. In this study using a qualitative method that aims to find a way out of challenges and opportunity in preaching by relying on information technology and based on the results of research, preaching during the pandemic in the village of Lampuja continues as usual but by complying with government recommendations and implementing health protocols with the help of the use of information technology be able to reach and convey da'wah messages quickly and widely.